2013
DOI: 10.1111/pcn.12079
|View full text |Cite
|
Sign up to set email alerts
|

One‐year follow up after admission to an emergency department for drug overdose in Japan

Abstract: Aim:The aim of the study was to investigate the incidence of and risk factors for repetition of suicidal behavior within a year after admission for drug overdose in Japan.Methods: Patients admitted to the emergency department of a general public hospital in Tokyo for drug overdose of prescribed medicine and/or over-thecounter drugs between March 2008 and February 2009 were followed up after 1 year. Demographic characteristics, previous suicide attempts, and mental health state were examined by self-report ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…4 We found that medicines containing barbiturates were overdosed by a substantial proportion of patients in Japan, and it was associated with serious outcomes. In a survey of all 190 patients (mean age 32.6 ± 0.95 years) who admitted to an emergency department in 1 year due to drug overdose between 2008 and 2009, 5 overdosed medicines were examined by interviewing patients and cohabitants and by urinary triage if conducted. Among 185 patients whose kinds of overdosed drugs were revealed, 29 patients (15.7%) overdosed medicines containing barbiturates.…”
mentioning
confidence: 99%
“…4 We found that medicines containing barbiturates were overdosed by a substantial proportion of patients in Japan, and it was associated with serious outcomes. In a survey of all 190 patients (mean age 32.6 ± 0.95 years) who admitted to an emergency department in 1 year due to drug overdose between 2008 and 2009, 5 overdosed medicines were examined by interviewing patients and cohabitants and by urinary triage if conducted. Among 185 patients whose kinds of overdosed drugs were revealed, 29 patients (15.7%) overdosed medicines containing barbiturates.…”
mentioning
confidence: 99%
“…Forty studies were further excluded because of identical or overlapping patient samples. A total of 115 studies reporting 167 samples were included in the meta‐analysis (SM 2, Table of Included Studies, and SM 3 Data used in meta‐analysis). The samples included 46 samples of females, 46 samples of males and 75 samples of both sexes.…”
Section: Resultsmentioning
confidence: 99%
“…Intentional drug overdose was de ned as the intentional self-administration of more than twice prescribed dose of a medicine and/or over-the-counter drug at one time. 4 Recurrence was de ned as a repeated episode of an intentional overdose that required for hospitalization within 1 year of discharge. 4 Recurrence was detected from medical record when they transferred to the hospital.…”
Section: Study Setting and Patientsmentioning
confidence: 99%
“…The main predictor of future suicidal behavior is a previous suicide attempt. [3][4][5] A strategy to reduce the recurrence of suicide attempts is needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation